Repeat genital Chlamydia trachomatis testing rates in young adults in England, 2010. Issue 1 (1st September 2012) - Woodhall, Sarah C; Atkins, Janice L; Soldan, Kate; Hughes, Gwenda; Bone, Angie; Gill, O Noel
Abstract : Objectives: To explore patterns of repeat chlamydia testing among young people in England and factors associated with testing positive at repeat test. Methods: We analysed chlamydia testing among 15 to 24-year-olds in England in a single calendar year (2010) using data from the genitourinary medicine clinic activity dataset (GUMCAD) and tests reported through the National Chlamydia Screening Programme (NCSP). Case records were linked using patient clinic numbers (GUMCAD), or by matching date of birth, gender and postcode (NCSP). Individuals could not be linked between datasets. The incidence of repeat testing was estimated using survival analysis. Risk factors for testing positive at repeat test were explored using multivariable logistic regression. Results: 1 235 058 tests in the NCSP dataset and 502 095 in GUMCAD were included. The incidence of repeat testing was 18.4 and 26.1 per 100 person years in the NCSP dataset and GUMCAD respectively. Among NCSP repeat tests, the proportion testing positive was higher in those reporting recent change of sexual partner (adjusted OR males 1.44; females 1.52), and among those with a positive compared to a negative baseline test (adjusted OR males 2.57; females 1.95). Conclusions: We observed moderate levels of repeat testing within a year. Considering the frequency of partner change among young people, more could be done to encourage re-testing upon change of sexual partner. Increasing re-testing following a positive test could probably identify unresolved or repeat infections that may otherwise go untreated. Work to establish the optimum approach to repeat testing in England is now warranted.